KOMPARASI POTENSI HASIL DARI BEBERAPA VARIETAS UNGGUL PADI SAWAH - Kiki Kusyaeri Hamdani; Yati Haryati (Agric, 2021)
New superior varieties (VUB) are a reliable technological innovation to increase rice productivity. This study aims to determine the yield potential of some lowland rice VUB. The assessment was carried out on land owned by a member of the Sumber Rejeki Farmer Group, Cintaratu Village, Lakbok District, Ciamis Regency at Dry Season II in June-September 2020. The study used a randomized complete block design (RCBD) with six varieties of treatment and was repeated ten times. The varieties tested were Inpari 32, Inpari 42, Padjadjaran, Cakrabuana, Inpari IR Nutrizinc, and Siliwangi varieties. The variables observed included the growth component, yield component, and yield component. Data were analyzed using the F test followedby the Duncan Multiple Range Test at the Q=5% level. In addition, a correlation test was conducted between the growth components, yield components, and yields. The results of the study indicated that the new superior rice varieties studied had different performance in growth, number of tillers, yield, and yield components. Inpari 42 variety produced the highest productivity, namely 6.88 ton ha-1 which was supported by the number of grains per panicle, percentage of filled grains per panicle, and percentage of empty grain per panicle which were better than other varieties. Plant height and number of grains per panicle were positively correlated with yield.